Hi-C heatmap for the tetraploid genome of iuLoeVari1.µ. - Amjad Khalaf (22470183) (2025)
Hi-C contact maps are heatmaps that visualize the frequency of physical contacts between genomic regions in 3D-space. Regions that are closer together physically tend to show more interactions, appearing as darker colors on the map. The strongest signal, in dark red here, is always found along the diagonal, which represents self–self interactions (i.e., each genomic region interacting with itself and nearby regions along the same chromosome). Off-diagonal signals represent interactions between different chromosomes. (A) Hi-C contact map of the tetraploid iuLoeVari1.µ genome (host Loensia variegata [Psocodea]). Each chromosome, with its four copies, is highlighted by a yellow box. (B) Hi-C contact map showing the interactions amongst the four copies of chromosome 1 and the four copies of chromosome 2. Green lines highlight interactions belonging to unit 1, and purple lines highlight interactions belonging to unit 2. Dotted lines indicate interactions between chromosomes 1 and 2. (C) Summary metrics for the genome assemblies of units A/B and C/D. The data underlying this figure was generated by mapping the Hi-C reads to the genome using the sanger-tol/curationpretext pipeline [102] (excluding multi-mapping reads). The genome can be found in File Collection 12 at https://doi.org/10.5281/zenodo.17251512. The genome’s BioSpecimenID can be found in S1 Table, and can be used to retrieve the associated Hi-C reads from NCBI [99]. The figure was generated using PretextView [103], and manually annotated using InkScape (version 1.2.2).